Study of the critical behavior of the driven lattice gas model with limited nonequilibrium dynamics - Saracco, Gustavo Pablo (2017)
In this paper the nonequilibrium critical behavior is investigated using a variant of the well-known two-dimensional driven lattice gas (DLG) model, called modified driven lattice gas (MDLG). In this model, the application of the external field is regulated by a parameter pϵ[0, 1] in such a way that if p = 0, the field is not applied, and it becomes the Ising model, while if p = 1, the DLG model is recovered. The behavior of the model is investigated for several values of p by studying the dynamic evolution of the system within the short-time regime in the neighborhood of a phase transition. It is found that the system experiences second-order phase transitions in all the interval of p for the density of particles ρ = 0.5. The determined critical temperatures Tc (p) are greater than the critical temperature of the Ising model T I c , and increase with p up to the critical temperature of the DLG model in the limit of infinite driving fields. The dependence of Tc (p) on p is compatible with a power-law behavior whose exponent is ψ = 0.27(3). Furthermore, the complete set of the critical and the anisotropic exponents is estimated. For the smallest value of p, the dynamics and β exponents are close to that calculated for the Ising model, and the anisotropic exponent ∆ is near zero. As p is increased, the exponents and ∆ change, meaning that the anisotropy effects increase. For the largest value investigated, the set of exponents approaches to that reported by the most recent theoretical framework developed for the DLG model.